THE EFFECT OF CURRENT RATIO, DEBT TO EQUITY RATIO, AND ENTERPRISE RESOURCE PLANNING ON FINANCIAL PERFORMANCE - Trisandi Eka Putri; Leny Marlina Nurhayati; Bambang Sugiharto (JASS (Journal of Accounting for Sustainable Society), 2025)
Intermediate Financial Accounting is a continuation of This study aims to examine the effect of the Current Ratio (CR), Debt to Equity Ratio (DER), and the implementation of Enterprise Resource Planning (ERP) on the financial performance of manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2023–2024 period. Financial performance is proxied by Return on Assets (ROA) as the main indicator of profitability. The research is based on the Resource-Based View (RBV) theory, which emphasizes that competitive advantage can be achieved through effective management of valuable, rare, inimitable, and well-organized internal resources. This research employs a quantitative method using secondary data obtained from the financial statements of manufacturing companies listed on the IDX. The sample was determined using purposive sampling with specific criteria, resulting in 60 companies or 99 observations. Data analysis was conducted using multiple linear regression with SPSS 23, accompanied by classical assumption tests to ensure model validity. The findings are expected to show whether CR, DER, and ERP have a partial or simultaneous influence on ROA. The results provide theoretical contributions to the literature on the relationship between financial ratios, information technology, and profitability in the manufacturing sector, as well as practical benefits for company management in making strategic decisions related to liquidity, capital structure, and ERP implementation.